2022
DOI: 10.1007/s41230-022-1007-4
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening CoCrFeNi high-entropy alloy by Laves and boride phases

Abstract: To strengthen the face-centered-cubic (FCC) type CoCrFeNi high-entropy alloy (HEA) by in-situ reinforced phase, (CoCrFeNi) 100-x (NbB 2 ) x (x=0, 2, 4, 6, 8, at.%) alloys were prepared. Phase constitution, microstructure, tensile mechanical properties of the alloys were studied, and the mechanisms were discussed. Results show that the microstructure of all the reinforced alloys consists of the matrix FCC phase, Laves phase, and (Cr 3 Fe)B x phase. The eutectic structure and (Cr 3 Fe)B x phases are formed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…On the other hand, the addition of Nb in high-entropy alloys (HEAs) has a significant impact on the formation of Laves phases. Research has shown that Nb can promote the formation of Laves phases in various HEAs, such as CoCrFeNi and CoCrFeMnNi alloys (Chen et al, 2022). The presence of Nb-rich Laves phases in these alloys contributes to strengthening mechanisms, enhancing the overall mechanical properties of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the addition of Nb in high-entropy alloys (HEAs) has a significant impact on the formation of Laves phases. Research has shown that Nb can promote the formation of Laves phases in various HEAs, such as CoCrFeNi and CoCrFeMnNi alloys (Chen et al, 2022). The presence of Nb-rich Laves phases in these alloys contributes to strengthening mechanisms, enhancing the overall mechanical properties of the materials.…”
Section: Introductionmentioning
confidence: 99%